Hubungan antara Beban Kerja dengan Stress Kerja pada Karyawan Bagian Customer Service yang Berada pada Tahap Dewasa Awal di PT. SDN - Winne Herwine; Dewi Handayani Harahap; FX Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2024)
ABSTRACT This study aims to empirically examine the relationship between workload and job stress among Customer Service employees in early adulthood at PT. SDN. The study involved 35 Customer Service employees in early adulthood at PT. SDN as subjects. Data collection was conducted using a workload scale based on Ambar (2003) and a job stress scale based on Robbins & Judge (2008) with a product-moment correlation analysis. The results showed a very significant positive relationship between workload and job stress, with a correlation coefficient (r) = 0.676 and a significance value of 0.000 (p<0.01). Additional findings revealed that the task aspect of the workload variable contributed 15.5%, the support & facilities aspect contributed 19.9%, and the time & conditions aspect contributed 10.13%, resulting in a total effective contribution of 45.5%. Keywords: Workload, Job Stress, Early Adulthood